Association of Serum Ferritin Levels with Glycemic Control in type-2 Diabetes Mellitus - H.R, Chandrashekhar; H.S, Shekar; Nagaraju, Kiran; C, Chikkalingiah; C, Bhagavan B. (Indian Journal of Pharmacy Practice)
Several recent studies concluded that, serum ferritin was found to be high in uncontrolled type 2 diabetic patients. There is paucity of information regarding association of serum ferritin levels with glycemic control in type 2 diabetic patients in India. This study was undertaken to identify the serum ferritin levels in poorly controlled type 2 diabetic patients and in well controlled type 2 diabetic patients taken as controls. The case control study was conducted and compared serum ferritin levels in 50 poorly controlled type 2 diabetics with 50 well controlled type 2 diabetics as controls. Chi square, Student t-test, Pearson correlation and Fisher exact test were used for statistical analysis. There was statistically significant (p <0.001) elevation of serum ferritin levels (of about 66%) in poorly controlled type 2 diabetics compared to control group (4%). The elevation of serum ferritin levels in poorly controlled diabetics compared to control group and it was statistically significant (p <0.001). Additional observations showed the positive correlation of serum ferritin levels with fasting blood sugar, post prandial blood sugar, and glycosylated hemoglobin and body mass index. The study shows positive association of serum ferritin levels with glycemic control in Type 2 Diabetic patients.
Keywords: Diabetes mellitus; Glycemic control; Glycosylated haemoglobin; Fasting blood sugar; Post prandial blood sugar; Serum ferritin; Type 2 DM